Institutional investors, heterogeneous benchmarks and the comovement of asset prices - Buffa, Andrea M.; Hodor, Idan (Journal of Financial Economics, 2023)
We study the equilibrium implications of a multi-asset economy in which asset managers performance is tied to different benchmarks, reflecting heterogeneity in their investment mandates. Fluctuations in the capital asset managers invest for benchmarking purposes, scaled by the size of the economy, induce price pressure that results in negative spillovers across assets. We characterize a rich structure of asset price comovement within and across benchmarks by analyzing shock elasticities and cross-elasticities of price-dividend ratios. Evidence on the heterogeneity of mutual fund mandates and the benchmarking-induced return comovement across cap-style and industry-sector portfolios corroborates the model assumptions and predictions.